2023
DOI: 10.2147/idr.s403441
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Quorum Sensing and Virulence Factor Genes Among Pseudomonas aeruginosa Isolated from Patients Suffering from Different Infections and Their Association with Antimicrobial Resistance

Abstract: Purpose Antimicrobial resistance and virulence genes play important roles in increasing the severity of Pseudomonas aeruginosa infections, especially in hospitalized patients with high antibiotic pressure. Most genes that encode Pseudomonas aeruginosa virulence factors are controlled and regulated by the quorum sensing (QS) system. The aim of this study was to investigate the frequency of some virulence genes ( rhlR, rhlI, lasR, l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 48 publications
2
6
0
Order By: Relevance
“…This finding was in line with previous studies that reported varying frequencies of gelatinase production in P. aeruginosa isolates from clinical sources [18,19]. The presence of gelatinase in wound and urine samples, indicating its potential role in tissue damage and urinary tract infections, was supported by previous research that implicated gelatinase in P. aeruginosa pathogenesis [20,21].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This finding was in line with previous studies that reported varying frequencies of gelatinase production in P. aeruginosa isolates from clinical sources [18,19]. The presence of gelatinase in wound and urine samples, indicating its potential role in tissue damage and urinary tract infections, was supported by previous research that implicated gelatinase in P. aeruginosa pathogenesis [20,21].…”
Section: Discussionsupporting
confidence: 92%
“…When comparing these results with previous studies, it is evident that the inhibitory effects of P. aeruginosa strains can vary among different environmental sources and target pathogens. These data suggest the presence of different antimicrobial mechanisms employed by the strains [ 20 , 21 ]. Further research is needed to understand these mechanisms and their potential applications in combating pathogens.…”
Section: Discussionmentioning
confidence: 99%
“…As anticipated, the presence of this gene was observed in all strains, exhibited biofilm production, and demonstrated varying levels of resistance to antimicrobial agents. Other studies corroborate ours in relation to the high percentage of detection of toxA and algD genes [63,64] lasB genes were found in all strains, while lasA genes appeared in 26.32% of isolates. Usually, these genes encode proteins secreted by the type II secretion system, which plays a major role during infection.…”
Section: Detection Of Virulence Genessupporting
confidence: 89%
“…This observation implies that P. aeruginosa exhibits a diverse repertoire of lasB enzymes, which have likely evolved to accommodate various environments and hosts. The prevalence of lasB in other studies is also high, which indicates that, in isolates of P. aeruginosa, this gene is highly distributed [63,64,66]. Variation in lasA gene recognition may influence the specific populations and clinical settings studied.…”
Section: Detection Of Virulence Genesmentioning
confidence: 97%
See 1 more Smart Citation